Existence and mathematical analysis of a coupled nonlinear system. (June 2022) - Cavalcanti, Marcelo M.
Abstract: In this paper we study the existence and uniqueness of local solutions for the coupled nonlinear system u ′ ′ − Δ u + M ∫ Ω | ∇ u | 2 d x Δ u + v = f v ′ − Δ v + u ′ = g for bounded or unbounded domains making use of the diagonalization theorem for self-adjoint operators.